2023
DOI: 10.31557/apjcp.2023.24.3.769
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Impact of Fatigue on Quality of Life (QOL) of Cancer Patients Undergoing Chemotherapy: A Systematic Review and Meta-Analysis

Abstract: Background: Fatigue is a typical consequence of cancer that can affect one's quality of life (QOL). The goal of this review is to provide comprehensive data on the impact of fatigue on QOL of cancer patients. Methods: An electronic data search in Web of Science, SCOPUS, and PubMed for relevant papers; those written in English; those reporting quantitative data; and those including more than one hundred patients who received just chemotherapy were included. Studies involving participants that received other kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…It has even been found that patients infected with the novel coronavirus have subsequent complications of cognitive impairment(21)(22) (23). It is thought that hypoxemia causes structural changes in the brain, or that in ammatory factors or cellular damage may play a role(24) (25). However, it may be di cult to study the mechanisms involved in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It has even been found that patients infected with the novel coronavirus have subsequent complications of cognitive impairment(21)(22) (23). It is thought that hypoxemia causes structural changes in the brain, or that in ammatory factors or cellular damage may play a role(24) (25). However, it may be di cult to study the mechanisms involved in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Although various studies presented the results of LE and WW in treating patients with locally advanced rectal cancer, reliable data comparing the outcomes of these two approaches are still lacking [ 29 ]. In part, the reason WW and LE are difficult to compare is the need to consider different outcomes, including survival, relapses, and QoL variables [ 30 , 31 ]. In this framework, the win statistics could easily consider both classical efficacy and QoL outcomes, providing a comprehensive evaluation of treatment benefits and drawbacks.…”
Section: Methodsmentioning
confidence: 99%